Design and high-strength origin of novel (CoFeNi)80Ti5V15 medium entropy alloy with "fcc + L12" structure. (20th June 2023) - Wang, Lei; Wu, Xinyuan; Wu, Yuan; Liu, Gang; Han, Zhenhua; Zhang, Yunpeng; Su, Yanning; Kang, Shengfeng; Shen, Jun; Zhang, Guojun
Highlights: It provides a novel idea to design an MEA with the "fcc+L12 " structure ((CoFeNi)80 Ti5 V15 ). MEA is cold rolled followed by aging (SCA) to keep high strength (YS/UTS ∼1395/1565 MPa). SCA alloy consists of non-recrystallization (L12 ) and recrystallization region (η). High-density SFs are commonly observed in the present unformed SCA alloy. High strength of SCA alloy mainly stems from L12, η precipitate, and high-density SFs. Abstract: This study provides a good design idea to obtain a novel (CoFeNi)80 Ti5 V15 medium entropy alloy with a "face center cubic (fcc) + L12 " structure by substituting equiatomic CoFeNi for Co in the Co80 Ti5 V15 superalloy and using the conventional thermomechanical processing method (solution+cold rolling+recrystallization annealing+aging, SCRA). In order to obtain superior strength, the recrystallization annealing procedure is removed (SCA), thus resulting in the formation of heterogeneous structures consisting of the recrystallization region and non-recrystallization region. In the recrystallization region, the grain consists of fcc matrix and η lamellar phase. In the non-recrystallization region, the high-density nanoscale L12 precipitates are uniformly distributed. The SCA (CoFeNi)80 Ti5 V15 alloy exhibits a rather high yield strength of ∼1395 MPa and ultimate tensile strength of ∼1565 MPa together with acceptable tensile elongation of ∼9%. The high strength of SCA alloy originates from the L12 nano-precipitates, η lamellar precipitates, high-density SFs, heterogeneous structure, dislocation, and grain refinement strengthening.